2009
DOI: 10.1002/jcu.20629
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic diagnosis and monitoring of an intramural duodenal hematoma following upper endoscopic biopsy in a child

Abstract: Intramural duodenal hematoma is an uncommon complication of pediatric endoscopic biopsy that occurs mainly in children with bleeding disorders. We report the case of a 5-year-old girl who presented with signs of partial duodenal obstruction and acute pancreatitis due to duodenal hematoma following endoscopic biopsy. The lesion was diagnosed and monitored by sonography and resolved with conservative management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
0
7
0
2
Order By: Relevance
“…Some authors have suggested that a particular anatomy of the duodenum or of its vascularization could be the explanation for the higher incidence of this pathology in the young . Regardless of this hypothesis, as the number of endoscopic biopsies increases, it becomes clear that the number of cases of iatrogenic duodenal hematoma in healthy children may also increase …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have suggested that a particular anatomy of the duodenum or of its vascularization could be the explanation for the higher incidence of this pathology in the young . Regardless of this hypothesis, as the number of endoscopic biopsies increases, it becomes clear that the number of cases of iatrogenic duodenal hematoma in healthy children may also increase …”
Section: Discussionmentioning
confidence: 99%
“…Multislice imaging techniques such as CT or, preferably, MRI, may be useful in equivocal situations, as they both correctly identify fresh blood or blood products . However, proper taking of history and analysis of the sonographic findings make these techniques unnecessary in most cases …”
Section: Discussionmentioning
confidence: 99%
“…It is a rapid, noninvasive test, does not expose the patient to ionizing radiation and, in combination with plain film, can often exclude the diagnosis of perforation. 4 Additionally, ultrasound is an excellent adjunctive tool to be used in monitoring the size and subsequent resolution of a hematoma, as was done in the patient in our case study. The majority of patients with IDH are managed conservatively; surgical treatment is commonly reserved for those who have perforation.…”
Section: Discussionmentioning
confidence: 90%
“…[2][3][4][5][6] However, ultrasound has become an effective, initial screening tool used in the diagnosis of IDH and has several benefits. It is a rapid, noninvasive test, does not expose the patient to ionizing radiation and, in combination with plain film, can often exclude the diagnosis of perforation.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound provides immediate information about the presence and the age of the haematoma. It is also used serially to observe the resolution of the haematoma [34]. Upper gastrointestinal series describe well the duodenal obstruction and may also demonstrate perforation.…”
Section: Discussionmentioning
confidence: 99%